Can nature promote development? The role of sustainable tourism for economic growth - Andreas Freytag; Christoph Vietze (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2010)
We analyze whether biodiversity is enhancing the development process in developing countries (DCs) via increasing tourism receipts in a trade based endogenous growth framework. The underlying assumption is that a rich biodiversity - only if used sustainably - provides a comparative advantage in tourism for most DCs. The main empirical findings are that biodiversity while being significantly and positively correlated with inbound tourism receipts in DCs, has no significant relation with tourist arrivals. This can be interpreted as an indicator that mass tourism is not influenced by biodiversity whereas individual tourism (as the superior good) is. Consequently, we are able to show empirical a positive influence of sustainable tourism on economic growth. Therefore, it may be a promising development strategy to invest in biodiversity and attract high budget tourists.
Keywords: F18; Q26; 330; tourism; economic growth; sustainable development; biodiversity conservation; cross country analysis; Biodiversität; Öko-Tourismus; Wirtschaftswachstum; Nachhaltige Entwicklung; Entwicklungsländer